ChemInform Abstract: Synthesis and Biological Evaluation of Novel Pyrazole Derivatives as Antibacterial Agents. Issue 12 (14th March 2013) - Daemi, Fariba; Allameh, Sadegh; Pordel, Mehdi
Abstract Concerning the antibacterial activity against MRSA, derivatives (VIc) and (VIe) display promising potency in the range of cephalexin, cloxacillin, and erythromycin.